Asymptomatic bacteriuria in children with sickle cell anemia at The University of Nigeria teaching hospital, Enugu, South East, Nigeria - Ikefuna Anthony N; Okafor Henrietta U; Chukwu Bartholomew F (BMC, 2011)
Abstract Background Urinary tract infection (UTI) is a common cause of childhood morbidity and mortality in the tropics. Children with sickle cell anemia (SCA) may have compromised kidney function arising from repeated vaso-occlusive episodes and recurrent symptomatic or asymptomatic UTI. Objectives This study aims at determining the prevalence of asymptomatic bacteriuria and sensitivity pattern in children with homozygous sickle haemoglobin compared to children with normal haemoglobin. Methods One hundred children with SCA in stable state and 100 children with normal haemoglobin aged 2-12 years were screened for asymptomatic bacteriuria using midstream urine samples. The samples were incubated aerobically at 37°C for 24 hours within one hour of collection. Children whose urine samples yielded significant bacteriuria (≥105cfu/ml) on two consecutive cultures were regarded as having asymptomatic bacteriuria. Results Asymptomatic bacteriuria was noted in 6% of children with SCA and occurred more in females than males (F: M = 5:1) when compared to 2% in children with normal haemoglobin. Escherichia coli was the commonest organism isolated (33.3%). All the organisms were resistant to co-trimoxazole and ampicillin while most were sensitive to gentamicin, ceftriaxone and the quinolones. Conclusion The risk of asymptomatic bacteriuria is three times more common in children with sickle cell anemia than in children with normal haemoglobin. It is therefore important to screen SCA patients, especially the females for UTI and should be treated according to the sensitivity result of the cultured organisms.